Direct and indirect bronchoprovocation tests in dose‐response studies of inhaled corticosteroids: Past, present, and future directions. Issue 6 (24th November 2020) - Blais, Christianne M.; Davis, Beth E.; Nair, Parameswaran; Cockcroft, Donald W.
Abstract: Inhaled corticosteroids (ICS) are a mainstay of treatment in eosinophilic asthma. Many studies have explored the dose‐response effect of different formulations of ICS through direct or indirect bronchoprovocation testing. Such studies are important for investigating efficacy and identifying the relative potency between formulations. However, lack of consistency in methods and designs has hindered the comparability of study findings. This review discusses current knowledge of the dose‐response, or lack thereof, of different formulations of ICS through direct and indirect bronchoprovocation testing. The strengths and weaknesses of past studies inform recommendations for future methodological considerations in this field, such as utilizing a randomized double‐blind crossover design, enrolling participants likely to respond to ICS therapy, and carefully selecting treatment durations and washout periods to assess incremental improvement in airway hyperresponsiveness while reducing the likelihood of a carryover effect.